Beyond the representative agent - Kirman, A. P.; Gallegati, M. (Mauro) (Cheltenham, UK ; Northampton, MA : Edward Elgar, 1999)
This challenging book extends standard economic theory to take into account the presence of heterogeneity among economic agents. It argues for an approach to economic analysis which regards the economy as an interactive system which treats aggregates as some representative individual. The authors find that this approach proves much more fruitful in explaining empirical phenomena than much of the economy which is at odds with common sense, but which does not abandon rigorous analysis. This important book will be welcomed by those interested in both macro and micro economic theory.
Includes bibliographical references and index.
rpm 12/11/13
Loans
Keywords: Social interaction; Macroeconomics; Economics -- Sociological aspects